“Difference” in the Qur’an (American Journal of Islam and Society, 2009)
This article seeks to explain and analyze the concept of cultural ikhtilaf (difference)in the Qur’an. Islam introduces a model for human communicationamong cultures at the individual and group levels that is based on humanvalues that guarantee a person’s dignity and human rights. The principle ofdifference in Islam means accepting the “other,” namely, the different person,by establishing relations based on acquaintance, dialogue, sharing, andreciprocity. Difference became an important conceptual tool in the frameworkof traditional Muslim societies’willingness to accept diversity and hasremained an important part of Muslim discourse.1The different person is not a mere independent isolated unit living withinhis/her own world and whose main concern is to protect himself/herselfand his/her identity from loss and forgetfulness. Rather, he/she is characterizedby his/her communicative and productive nature and entity, which aredelineated by mutual dependence on the “other” while maintaining the independenceof the “other.” The “other” also has an independent and confidentcharacter that qualifies him/her to establish a communicative and reciprocalrelationship that seeks to achieve public advantage.The “different” person can prove his/her truth, since “difference” is usedin a saying based on evidence,2 and the established truth based on this evidencegrants its holdermoral and logical confidence, therebymaking him/hermore open to the “other.” In addition, evidence indicates the power of argumentativelogic and high epistemological level of those who differentiate.The concept of difference, while based on rationality and logic, also carriesa moral dimension as a complementary unity.As a result, therefore, differenceturns out to be a fundamental element in establishing a civilized creativesociety ...